(untitled) (Anwer Khan Modern Medical College Journal, 2011)
This is a case report of a middle aged man who presented with weight loss and epigastric pain. The initial diagnosis was space occupying lesion in liver. The mass was later demonstrated by trans-abdominal percutaneous needle biopsy to be an abscess caused by Ascaris lumbricoides. Fertilized Eggs and Larvae of Ascaris lumbricoides was found. Key Words: Liver Abscess; Ascaris Lumbricoides DOI: 10.3329/akmmcj.v1i2.7462 Anwer Khan Modern Medical College Journal 2010; 1(2): 25-26